Antioxidant Activity and Biological Activity of Specialty Barley (Hordeum vulgare L.) Extracts - Lee, N.Y., National Institute of Crop Science, RDA, Iksan, Republic of Korea; Kim, Y.K., National Institute of Crop Science, RDA, Iksan, Republic of Korea; Choi, I.D., National Institute of Crop Science, RDA, Iksan, Republic of Korea; Cho, S.K., National Institute of Crop Science, RDA, Iksan, Republic of Korea; Kweon, H.J., Apple Experiment Station, National Institute of Horticulture and Herbal Science, RDA, Gunwi, Republic of Korea; Lee, K.W., National Institute of Crop Science, RDA, Iksan, Republic of Korea; Hyun, J.N., National Institute of Crop Science, RDA, Iksan, Republic of Korea; Choi, J.S., National Institute of Crop Science, RDA, Iksan, Republic of Korea; Park, K.H., Rural Development Administration, Suwon, Republic of Korea; Kim, K.J., National Institute of Crop Science, RDA, Iksan, Republic of Korea; Lee, M.J., National Institute of Crop Science, RDA, Iksan, Republic of Korea (Korean journal of crop science, 2010)
Specialty barley extracts were prepared and investigated for its antioxidant activity and biological activity. Hunter L* values of the Iksan 86 extracts had higher than that of the Iksan 87 and Zasoojeongchal extracts. The extraction yields of Iksan 86, Iksan 87, and Zasoojeongchal was 8.08, 6.62, and 7.30%, respectively. The contents of total phenolic compounds of the Iksan 86, Iksan 87, and Zasoojeongchal extracts were 16.24, 15.51, and 13.95 GAE mg/g of sample, respectively. The DPPH radical scavenging activity of Iksan 86, Iksan 87, and Zasoojeongchal extracts were 50.00, 33.27, and 7.56% at a 500 ppm, respectively. The samples showed an inhibition of xanthin oxidase. ACE inhibition effect of specialty barley extracts, Iksan 86, Iksan 87, and Zasoojeongchal, was 39.81, 41.06, and 27.78%, respectively. Tyrosinase inhibition rates (%) of Iksan 86, Iksan 87, and Zasoojeongchal extracts were 26.21, 24.57, and 20.00%, respectively. Results indicated that specialty barley extracts possesses various biological activities including antioxidative capacity, xanthin oxidase inhibition activity, angiotensin converting enzyme inhibition activity, and tyrosinase inhibition activity.